Carotid intima-media thickness, 25-OH vitamin D, homocysteine and subclinical coronary artery atherosclerosis in patients with type 1 diabetes mellitus - Milić, Gordana; Gačić, Jasna; Mladenović-Marković, Ana; Soldatović, Ivan; Matić, Dragan; Popović, Srđan; Marković, Željko; Damjanović, Svetozar (Archives of Biological Sciences, 2019)
Paper description: The predictive significance of elevated plasma total homocysteine, lower serum 25-hydroxy vitamin D and increased carotid intima-media thickness for development of coronary atherosclerosis in patients with type 1 diabetes and no previous history of ischemic heart disease was evaluated. This cross-sectional study included 73 diabetic patients, duration of diabetes over 5 years, age 19-40 years, with and without non-obstructive coronary artery stenosis. Hyperhomocysteinemia, lower serum vitamin D and increased carotid intima-media thickness present a higher risk of developing atherosclerosis. Homocysteine concentration is a reliable predictor for the development of coronary artery atherosclerosis in asymptomatic patients with type 1 diabetes. Abstract: Individuals with type 1 diabetes have an increased risk of premature atherosclerosis. The aim of this study was to evaluate the possible predictive significance of elevated plasma total homocysteine (tHcy), lower serum 25-hydroxy vitamin D (25(OH)D) concentrations and increased carotid intima-media thickness (CIMT) for the development of coronary atherosclerosis in patients with type 1 diabetes mellitus (T1D) and no previous history of ischemic heart disease. The study included 73 patients previously diagnosed with T1D. The patients were divided into groups with and without non-obstructive moderate coronary artery stenosis. Coronary artery stenosis was examined using coronary multidetector computed tomographic angiography (MDCTA); CIMT was measured by B-mode ultrasound. The patients with moderate stenosis had significantly higher HbA1c (p<0.001), elevated tHcy (p<0.001), increased CIMTmax. (p<0.001) but lower 25(OH)D (p<0.001) in comparison to patients without detectable coronary atherosclerosis. Homocysteine (AUCHcy=0.955; p<0.001), vitamin D (AUCvit D=0.792; p<0.001) and CIMT max (AUCCIMT=0.743; p<0.001) (AUC or area under the curve) appear to be adequate markers for detecting stenosis of coronary arteries using receiver operating characteristic (ROC) curve analysis. Multivariate logistic regression analysis showed that serum homocysteine was the only significant predictor of moderate coronary artery stenosis. Our study implies that tHcy can be used as a reliable predictor of coronary artery atherosclerosis in patients with T1D. 25(OH)D and CIMT can also be used, but with lower diagnostic accuracy. https://doi.org/10.2298/ABS190706048M Received: July 6, 2019; Revised: August 12, 2019; Accepted: August 20, 2019; Published online: August 28, 2019 How to cite this article: Milić G, Gačić J, Mladenović-Marković A, Soldatović I, Matić D, Popović S, Marković Ž, Damjanović S. Carotid intima-media thickness, 25-OH vitamin D, homocysteine and subclinical coronary artery atherosclerosis in patients with type 1 diabetes mellitus. Arch Biol Sci. 2019;71(4):655-63.